Grammatical ability and functional hearing in various listening conditions in 4–6-year-old children with prelingual unilateral hearing loss: a pilot study - Hedström, Ingrid; Löfkvist, Ulrika (Frontiers in Pediatrics, 2025)
ObjectivesThis pilot study aimed to investigate receptive and expressive grammatical abilities and functional hearing in everyday listening conditions among 4–6-year-old children with prelingual unilateral hearing loss (UHL), compared with peers with normal hearing (NH). A further aim was to explore whether grammatical abilities were associated with functional hearing and background factors such as severity and side of hearing loss, or parental education.MethodsEight children with UHL were recruited from hearing care clinics, and sixteen children with NH were recruited via social media. Data included questionnaires on hearing, development, and environment, and parent-reported functional hearing using PEACH+. Grammatical abilities were assessed with TROG-2 and the Swedish Gramba test. Group differences were analyzed with Mann–Whitney U-tests, and correlations were evaluated with Spearman's rank correlation.ResultsChildren with UHL scored lower than NH peers on language tests, though the differences were not statistically significant. They scored significantly lower on three of four parent-reported measures of functional hearing, particularly in noisy environments. Grammatical ability did not correlate with functional hearing. Across the cohort, higher parental education was associated with better grammatical outcomes. Within the UHL group, right-sided hearing loss was associated with poorer expressive grammar, and greater severity of hearing loss was associated with increased difficulty hearing in noise.ConclusionsChildren with UHL demonstrated poorer functional hearing and tended to have slightly reduced grammatical abilities compared to peers with NH. Although the small sample size limits generalizability, these findings, together with previous research, suggest potential impacts of UHL on language development. The side and severity of hearing loss may influence outcomes, highlighting the need for further research and international consensus on assessment and management.